2008
DOI: 10.1152/ajpregu.90345.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gonadectomy on AgRP-induced weight gain in rats

Abstract: Goodin SZ, Keichler AR, Smith M, Wendt D, Strader AD. Effect of gonadectomy on AgRP-induced weight gain in rats. Am J Physiol Regul Integr Comp Physiol 295: R1747-R1753, 2008. First published October 15, 2008 doi:10.1152/ajpregu.90345.2008.-Agouti-related peptide (AgRP), the endogenous antagonist to the melanocortin 3 and 4 receptors, elicits robust hyperphagia and weight gain in rodents when administered directly into the central nervous system. The relative influence of AgRP to cause weight gain in rodents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 24 publications
2
25
0
1
Order By: Relevance
“…Whether there were sex differences in these effects was not reported. Central injections of AgRP elicited similar effects on food intake and body weight in intact and gonadectomized male and female rats (131,281), however, suggesting that the malefemale sex difference in the effect of MC 4 receptor mutations described above is not related to AgRP function.…”
Section: Melanocyte-stimulating Hormones and Melanocortinmentioning
confidence: 84%
“…Whether there were sex differences in these effects was not reported. Central injections of AgRP elicited similar effects on food intake and body weight in intact and gonadectomized male and female rats (131,281), however, suggesting that the malefemale sex difference in the effect of MC 4 receptor mutations described above is not related to AgRP function.…”
Section: Melanocyte-stimulating Hormones and Melanocortinmentioning
confidence: 84%
“…For example, AGRP was reported to reduce energy expenditure (measured by vO 2 ) in female rats more than in male rats [181]. Removal of the gonads attenuated the observed differences in energy expenditure in females, suggesting sex hormones mediated the effect.…”
Section: Sex-specific Effects Of Melanocortin Ligandsmentioning
confidence: 99%
“…Removal of the gonads attenuated the observed differences in energy expenditure in females, suggesting sex hormones mediated the effect. Following icv administration, AGRP induced significantly elevated feeding for 5 days in males compared to only 3 days in female mice [181]. Lensing et al .…”
Section: Sex-specific Effects Of Melanocortin Ligandsmentioning
confidence: 99%
“…13 However, that study has been contradicted by several other reports that found no difference between male and female rodents with melanocortin ligands. 15, 20, 21 To further confound the understanding of the melanocortin ligands’ sex-dependent effects, many reports combine both sexes into their results, while others fail to indicate which sex was being studied.…”
Section: Introductionmentioning
confidence: 75%
“…13, 24 The RER is calculated by dividing the volume of CO 2 produced by an animal by the volume of O 2 consumed by the animal. 29, 30 This is calculated indirectly by the measuring the amount of CO 2 and O 2 entering and exiting the sealed metabolic cages.…”
Section: Resultsmentioning
confidence: 99%